Soil carbon stocks in Sarawak, Malaysia - Padmanabhan, Eswaran (2013)
The relationship between greenhouse gas emission and climate change has led to research to identify and manage the natural sources and sinks of the gases. CO2, CH4, and N2O have an anthropic source and of these CO2 is the least effective in trapping long wave radiation. Soil carbon sequestration can best be described as a process of removing carbon dioxide from the atmosphere and relocating into soils in a form that is not readily released back into the atmosphere. The purpose of this study is to estimate carbon stocks available under current conditions in Sarawak, Malaysia. SOC estimates are made for a standard depth of 100 cmunless the soil by definition is less than this depth, as in the case of lithic subgroups. Among themineral soils, Inceptisols tend to generally have the highest carbon contents (about 25 kg m−2 m−1), while Oxisols and Ultisols rate second (about 10–15 kg m−2 m−1). The Oxisols store a good amount of carbon because of an appreciable time-frame to sequester carbon and possibly lower decomposition rates for the organic carbon that is found at 1 m depths. Wet soils such as peatlands tend to store significant amounts of carbon. The highest values estimated for such soils are about 114 kg m−2 m−1. Such appreciable amounts can also be found in the Aquepts. In conclusion, it is pertinent to recognize that degradation of the carbon pool, just like desertification, is a real process and that this irreversible process must be addressed immediately. Therefore, appropriate soil management practices should be instituted to sequester large masses of soil carbon on an annual basis. This knowledge can be used effectively to formulate strategies to prevent forest fires and clearing: two processes that can quickly release sequestered carbon to the atmosphere in an almost irreversible manner.